STRUCTURE ANALYZE BUSHING OF CONTAINMENT RING USING NON-DESTRUCTIVE TEST FOR TURBOFAN OF AIR PLANES ENGINES - Muhammad Yusuf Nurfani (Asosiasi Dosen Muda Indonesia, 2023)
Containment ring is component on engine for turbofan engines of air plane. The function of Containment ring is for balancing assembly part as the shaft, retaining disk and fully bladed disk on turbofan of airplanes. The component of containment ring is bushing for join of part on engine. The joint process of production on bushing and ring using welding process. This study will discuss of structure analyze of welding area on containment ring using Non-Destructive Test (NDT). Method of analyze is additional chemical on welding area using ADROX for focusing crack are in material after welding process. The material of ring and busing is stainless steel FYNIS SUS304. The result show that welding areas of joint no any crack finding after 10 specimens tested of Containment ring. The checking method using additional chemical ARDROX 9814 (penetrant) in welding areas for inside and outside areas of the part.